Gender Wage Differentials and the Occupational Injury Risk - Evidence from Germany and the US - Jochen Kluve; Sandra Schaffner (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2007)
Numerous studies, in particular for the US, have shown that individuals in occupations with high injury risk are compensated for that risk by corresponding bonus payments. At the same time, male workers are overrepresented in the most dangerous occupations like scaffolders or miners, while females typically work in relatively safe occupations with respect to occupational injuries. It is therefore remarkable that almost all studies analyzing the gender wage gap have disregarded different occupational injury risks as a potential explanatory variable for observed gender wage differentials. By merging data on occupational injury risks to German and US panel data on individual workers, this study analyzes gender wage differentials in Germany and the US considering fatal occupational injury risk. The Blinder-Oaxaca method for tobit models is used to decompose the gender wage gap with and without consideration of the fatal injury risk. Our results indicate that the compensating wage differentials for risky jobs are reflected in the resulting gender wage gap, which is caused by the unequal distribution of occupational injury risks among men and women.
Keywords: J16; J17; J31; J7; 330; Gender wage differentials; occupational injury risk; compensating wage differentials; Blinder-Oaxaca decomposition; Lohnstruktur; Arbeitsunfall; Risiko; Lohndifferenzierung; Geschlecht; Deutschland; USA